Genre variation in student writing: A multi-dimensional analysis. Issue 22 (June 2016) - Hardy, Jack A.; Friginal, Eric
Abstract: EAP professionals often desire to better understand writing in the disciplines (WID) to inform their pedagogical materials and practices. While genre analysis has increased our understanding of academic writing, quantitative, corpus-based approaches can supplement the area (Biber, Connor, & Upton, 2007). To that end, a multi-dimensional (MD) analysis was conducted using dimensions extracted by Hardy and Römer (2013). Paper types from the Michigan Corpus of Upper-level Student Papers (MICUSP) were investigated along the following dimensions (1) Involved, Academic Narrative vs. Descriptive, Informational Discourse; (2) Expression of Opinions and Mental Processes; (3) Situation-Dependent, Non-Procedural Evaluation vs. Procedural Discourse; and (4) Production of Possibility Statement and Argumentation. The MICUSP paper types were found to pattern similarly across all four dimensions, with the more personal genres (e.g., creative writing, critiques/evaluations, response papers) and the more objective genres (e.g., research papers, reports) consistently averaging dimension scores on opposing ends of the poles. Highlights: A multi-dimensional analysis was conducted on MICUSP. Offers a better understanding of successful student writing. Gives a detailed understanding of how different student genres compare. Paper types across 16 disciplines pattern similarly across dimensions. Implications can be made for which genres to use in writing assignments.